2013
DOI: 10.1159/000354985
|View full text |Cite
|
Sign up to set email alerts
|

Therapy by Laser Equatorial Placental Dichorionization for Early-Onset Spontaneous Twin Anemia-Polycythemia Sequence

Abstract: We report a case of twin anemia-polycythemia sequence (TAPS) treated by fetoscopic laser equatorial placental dichorionization, also known as the ‘Solomon technique', at 24 weeks of gestation. TAPS was present despite the absence of fetoscopically visualized chorionic anastomoses from the donor to the recipient twin. The goal of this procedure was to prevent post-laser TAPS in cases of twin-twin transfusion syndrome. The surgery and subsequent intrauterine blood transfusion to the donor twin could result in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…These factors, along with case-specific features such as placental location, may make it difficult to identify all vascular communications and perform laser photocoagulation, which in turn can result in persistent or reversed sTAPS or TTTS if a vascular communication is missed. Furthermore, the potential benefits of fetoscopic laser surgery must be weighed against the possible procedure-related complications of operative fetoscopy, including premature rupture of membranes, disruption of the intertwin dividing membrane, and fetal demise [6,10,16]. Nevertheless, similar to our experiences, previous reports of fetoscopic laser treatment for TAPS have revealed that this treatment is effective [3,4,7,9,10,11,17].…”
Section: Commentsupporting
confidence: 73%
See 1 more Smart Citation
“…These factors, along with case-specific features such as placental location, may make it difficult to identify all vascular communications and perform laser photocoagulation, which in turn can result in persistent or reversed sTAPS or TTTS if a vascular communication is missed. Furthermore, the potential benefits of fetoscopic laser surgery must be weighed against the possible procedure-related complications of operative fetoscopy, including premature rupture of membranes, disruption of the intertwin dividing membrane, and fetal demise [6,10,16]. Nevertheless, similar to our experiences, previous reports of fetoscopic laser treatment for TAPS have revealed that this treatment is effective [3,4,7,9,10,11,17].…”
Section: Commentsupporting
confidence: 73%
“…Because of the relatively low prevalence and lack of clinical awareness, the natural history of this condition is unclear and the antenatal treatment of sTAPS remains controversial. Case series of sTAPS have described expectant management with timed delivery [5,6,7,8], intrauterine blood transfusion [4], and fetoscopic laser treatment [3,4,7,9,10]. Favorable outcomes have been described in cases of uncomplicated sTAPS that underwent expectant management or other conservative measures, particularly in cases diagnosed in the third trimester [5,7,8,11].…”
Section: Commentmentioning
confidence: 99%
“…It is a heterogeneous disorder, both in terms of its mode of onset [either after laser treatment of twin-twin transfusion syndrome (TTTS) or spontaneously] and its severity. There is no consensus about its antenatal management, and different therapeutic alternatives have been described: simple surveillance, intrauterine transfusion (IUT) of the anemic fetus possibly combined with partial exchange transfusion in the recipient, laser coagulation of the placental anastomoses, selective termination of pregnancy or fetal extraction [2,3,4,5,6,7,8,9,10,11]. On account of the low incidence of TAPS (1-5% of monochorionic diamniotic twin pregnancies for spontaneous TAPS [12,13,14,15] and 2-13% for iatrogenic TAPS [4,14,15,16]), therapeutic options have been presented only in case reports or small-size descriptive cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Several attempt to improve the perinatal outcome was made, such as intrauterine blood transfusion, selective feticide and placenta separation via fetoscopic laser coagulation [613]. Fetoscopic laser coagulation is the only fundamental form of therapy and Slaghekke et al [11] and Ishii et al [14] showed better perinatal outcome after laser coagulation especially in spontaneous TAPS in their retrospective cohort study. However, laser coagulation of TAPS is more difficult than that of TTTS.…”
Section: Discussionmentioning
confidence: 99%